Aspects of non-adiabatic molecular collision theory - Gover, M; M. R. Gover (1978)
﻿ This thesis is concerned with non-adiabatic effects in alkali / halogen collision systems. After a general survey of non-adiabatic molecular collision theory, and its application to such systems, calculations have been performed relating to three topics : (i) Vibrational energy distributions resulting from electron transfer collisions between alkali metal atoms and halogen molecules are often treated by the multi-curve crossing approach to the classical path approximation, in the form of two approximations, one valid at high collision energy, the other at low energy; the performance of these is evaluated over a wide energy range by comparison with the results from an "exact" multi-curve crossing approach. (ii) Classical trajectory calculations for reactive alkali / halogen collisions are performed using a simple ionic potential energy surface, developed earlier to model the weakening of the halogen bond by the metal ion immediately after the electron transfer. Detailed comparison is made between the results and those from experiment; good agreement is obtained for K/I2 and comparison of the results for K/I2 and Cs/I2 indicates that this effect is not merely dependent on the charge of the ion. (iii) The population of ground and excited sodium atoms resulting from Na/I charge neutralisation collisions is investigated using the multi-curve crossing approach. Although it has been suggested that population inversions may be produced by such a process, it is shown that this is only possible at extremely high collision energies.